História natural da rã-pimenta sul-americana, Leptodactylus labyrinthicus(Spix, 1824) (Anura: Leptodactylidae) - Silva, Wagner Rodrigues da (2005)
Some species of Leptodacíylus of the L. pentadaclylus group Iay their eggs outside water but the tadpoles need to reach water to complete the larval phase or complete development in terrestrial nests. Here we present details of the reproduction of L. labyrinthicus in SE Brazil. The proportion of tadpoles and trophic eggs in aged egg clutches was determined, as well as the growth of the tadpoles while in the nest. The gut contents of tadpoles that were in egg clutches of frogs were analyzed. Adult males did not differ from females in size and had hypertrophied forearms and an enlarged spine on the thumb. Reproduction was initiated with the first rains of August/September and extended to mid-January. Calling and spawning occurred at permanent or temporary water bodies. The foam nests were built in excavated basins outside of, but close to the water. The male determined the place of the basin construction; after amplexus, the female completed the excavation. The amplexus was axillary. One female spent the day after spawning in the foam. The eggs were pale grey, the yolk averaging 2.3 mm in diameter. The mean number of eggs was 2101 per egg clutch. The number of tadpoles in individual nests varied between 0.05% and 11.40% in relation to the total laid eggs. The tadpoles entered water when rains flooded the basin. The tadpoles incorporated until 12 times the weight of an individual egg while in lhe nest; no nesting tadpole was beyond stage 25. The longest time we followed tadpoles in a nest was 25 days. Tadpoles were found preying upon eggs of three olher frog species and upon conspecific eggs. Males fought by grasping each other in a belly-to-belly position; the powerful arms and the thumb spines represent weapons. All the species of the L. pentadaclylus group may build their foam nests within excavated basins. The basins may protect the eggs and embryos from cannibalistic tadpoles and may have an anti-desiccation effect. Anuran eggs represent an important food item for tadpoles after they leave the nest.